Analysis of Internal and External Factors Affecting the Performance of Village-Owned Enterprises (BUMDes): A Case Study of BUMDes Tungkap Jaya in Saka Village, East Kutai Regency - Tarisya Fitriani; B. Budiman; Dan Buntu Paranoan; J. Jumansyah (Manunggal Halim Jaya, 2026)
Village-Owned Enterprises (BUMDes) are strategic instruments for strengthening village economic independence and improving community welfare through sustainable management of local potential. This study aims to analyze the performance of BUMDes Tungkap Jaya in Saka Village, Sangkulirang District, East Kutai Regency. It identifies internal and external factors that hinder its operations and formulates recommendations for improving governance. This study uses a descriptive qualitative approach, with data collected through direct observation and in-depth interviews with BUMDes management, village officials, and community members. The results show that the performance of BUMDes Tungkap Jaya is not yet optimal, as indicated by the stagnation of its main business unit, ferry transportation services, from 2023 to 2025, even though it previously contributed significantly to the village economy and social mobility. Internal obstacles include low human resource capacity, weak business planning and strategy, inconsistent capital support, and limited community participation. Meanwhile, external obstacles consist of a lack of support from the village government and a low level of understanding of the regulatory and legal aspects related to BUMDes operations. This study concludes that optimizing the performance of BUMDes Tungkap Jaya requires comprehensive management improvements through increasing human resource capacity, strengthening business planning, consistent capital allocation, increasing support from the village government, improving regulatory understanding, and active community involvement. These efforts are expected to revive strategic business opportunities and position BUMDes as a sustainable driver for village economic development.